Green synthesis of silver nanoparticles using Laminaria japonica extract: Characterization and seedling growth assessment. (20th January 2018) - Kim, Dae-Young; Saratale, Rijuta Ganesh; Shinde, Surendra; Syed, Asad; Ameen, Fuad; Ghodake, Gajanan
Abstract: This study demonstrates a green route for the preparation of high-concentration suspensions of silver nanoparticles (AgNPs), by incubating AgNO3 with Laminaria japonica algal extract. The rate of AgNPs synthesis significantly increased within 2 min of initiating the incubation and elevating temperature from 90 °C to 120 °C. This method was also suitable for preparing AgNPs at ambient temperature but required 48–72 h for completion. A hydrothermal process (steam autoclave) resulted in accelerated temperature-controlled reduction of AgNO3 in which AgNO3 reduction to metallic AgNPs with robust control over optical and structural properties was successfully established using steam autoclaving at 100 kPa and 121 °C for 20 min. The process enabled a homogeneous reaction resulting in a narrow size distribution of AgNPs. Isotropic growth of AgNPs was evident under diverse synthetic conditions, designed considering various reaction factors including temperature, pH, extract concentration, and AgNO3 ratios. Freeze-drying was used to increase yield and shelf-life of the nanoproduct and prevent aggregation. The AgNPs showed no significant effects on seed germination of either Triticum aestivum and Phaseolus mungo . However, they influenced lengths of shoots and roots in both plant species in a dose-dependent manner. Graphical abstract: Image 1 Highlights: Laminaria japonica is an excellent resource for the production of high-concentration suspensions of AgNPs. High reducibility of the algal extract was strictly dependent on NaOH concentration. The hydrothermal mechanism was found suitable for commercial scale production. Excellent stability of the AgNPs was shown using re-dispersion studies of freeze dried powder. Seed germination assay suggested that the AgNPs were biocompatible across a broad concentration range.